Towards Sustainable Development through Higher Education Quality Assurance - Nataliia Stukalo; Maryna Lytvyn (MDPI AG, 2021)
This study aims to identify the role of higher education quality assurance in achieving sustainable development goals. To support this aim, the following objectives were formulated: to discuss and summarize the best practices of QA agencies in promoting SDGs, to identify how Ukrainian universities consider SDGs in their policies, to develop recommendations for internal, and external quality assurance systems regarding SDG achievement. This qualitative study is based on a case study, observation, and questionnaire methods. Ukrainian higher education quality assurance systems are taken as a case study for this article. Primary data are collected through an online questionnaire and observation of Ukrainian universities' publicly available information regarding sustainable development activities at their official websites. Additionally, some publicly available documents, reports, and materials on the experience of foreign quality assurance agencies are also reviewed, compared, and contrasted. The results of the research can be used at national levels where higher education standards should include competence in sustainable development goals, at institutional level to improve HEIs' quality assurance system, and at the study program level to include SDG consideration as one of the requirements during internal quality assurance procedures.